MoS2 Phototransistor Sensitized by Colloidal Semiconductor Quantum Wells. Issue 24 (28th October 2020) - Sar, Huseyin; Taghipour, Nima; Lisheshar, Ibrahim Wonge; Delikanli, Savas; Demirtaş, Mustafa; Demir, Hilmi Volkan; Ay, Feridun; Kosku Perkgöz, Nihan
Abstract: A phototransistor built by the assembly of 2D colloidal semiconductor quantum wells (CQWs) on a single layer of 2D transition metal dichalcogenide (TMD) is displayed. This hybrid device architecture exhibits high efficiency in Förster resonance energy transfer (FRET) enabling superior performance in terms of photoresponsivity and detectivity. Here, a thin film of CdSe/CdS CQWs acts as a sensitizer layer on top of the MoS2 monolayer based field‐effect transistor, where this CQWs–MoS2 structure allows for strong light absorption in CQWs in the operating spectral region and strong dipole‐to‐dipole coupling between MoS2 and CQWs resulting in enhanced photoresponsivity of one order of magnitude (11‐fold) at maximum gate voltage ( V BG  = 2 V) and two orders of magnitude (≈ 5 × 10 2 ) at V BG  = −1.5 V, and tenfold enhanced specific detectivity. The illumination power‐dependent characterization of this hybrid device reveals that the thin layer of CQWs dominates the photogating mechanism compared to the photoconductivity effect on detection performance. Such hybrid designs hold great promise for 2D‐material based photodetectors to reach high performance and find use in optoelectronic applications. Abstract : A substantial Förster resonance energy transfer‐assisted enhancement in photodetection performance of MoS2 phototransistors sensitized by colloidal semiconductor quantum wells (CQWs) is shown. As a model system, a thin film of CdSe/CdS core/crown CQWs is employed as sensitizer layer directly on MoS2 monolayer. By exploiting this architecture, ≈500‐fold enhancement in the photoresponsivity and tenfold in the detectivity ( D *) is achieved.